Treating Urge Incontinence in Older Women: A Cost-Effective Investment in Quality-Adjusted Life-Years (QALY). (3rd March 2015) - Phillips, Victoria L.; Bonakdar Tehrani, Ali; Langmuir, Holly; Goode, Patricia S.; Burgio, Kathryn L.
Abstract : Objectives . To conduct cost-effectiveness analyses of urge incontinence treatments for older women. Methods . Decision-analytic models assessed three treatment pathways: (1) limited behavioral therapy (LBT); (2) full behavioral therapy (FBT) with biofeedback; and (3) drug (DRUG), with allowances for crossover options following initial treatments. Model inputs were gathered from published data. Cost data were based on third party payer reimbursement. Outcomes were measured as the number of incontinence episodes avoided and quality-adjusted life years gained (QALYs). Results . At baseline values costs per QALY gained ranged from US$3696 to $10609. LBT was the least costly with the lowest benefit. Switching from LBT to FBT, with the greatest gain, was $415 per additional QALY. DRUG was the most expensive option. Sensitivity analyses showed that only small changes in key inputs were required for DRUG to generate greater gains than FBT. Medication costs had to fall substantially for DRUG to be cost competitive. Conclusion . All treatment strategies provide QALYs gains at a bargain price, compared to the standard of US$50, 000 per QALY gained. No single treatment strategy dominated under all conditions. Clinicians should offer multiple treatment options to older women with urge incontinence.